Facile fabrication of ordered discontinuous nanotopography on photosensitive substrates for enhanced neuronal differentiation. (17th June 2021) - Vinzons, Lester U; Lin, Shu-Ping
Abstract: Controlling the development and morphology of neurons is important for basic neuroscience research as well as for applications in nerve regeneration and neural interfaces. Various studies have shown that nanoscale topographies can promote the development of neuronal cells and the differentiation of neural stem cells; however, the fabrication of these nanotopographical features often involves expensive and sophisticated techniques. Here, we employ nanosphere lens lithography combined with UV-LED technology to create nanopatterns on an SU-8 photoresist. We develop a facile method to create a reusable polystyrene nanosphere (PS-NS) lens array by the spontaneous formation of a hexagonal close-packed array of PS-NSs at a water–air interface and its subsequent transfer to a polydimethylsiloxane carrier film without using any special equipment. We show that this simple technique can create ordered arrays of nanodots on an SU-8 film, the dimensions of which can be controlled by the size of the PS-NSs. When used as a substrate for the neuronal differentiation of pheochromocytoma (PC12) cells, the nanopatterned SU-8 films exhibit enhanced differentiation parameters with respect to conventional tissue culture plastic as compared with their flat counterparts. The method proposed here can greatly facilitate the nanopatterning of various photosensitive substrates for the development of implants for nerve regeneration and neural interfacing.